Implikasi Nilai-Nilai Moderasi Islam dalam Pembelajaran Pendidikan Agama Islam pada Siswa Sekolah Menengah Kejuruan (SMK) - Mashur, Mashur; Ulliyah , Navilah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2023)
The study of Islamic moderation in school institutions is very important associated with the learning of Islamic Religious Education as a control holder who has an important role in instilling moderation values from an early age. The type of research used is qualitative research. Data collection techniques in the form of observations where researchers make observations, interviews and documentation with descriptive-analytical analysis techniques. The results of the implementation of Islamic moderation values are by habitually applying Islamic moderation values, determining learning plan strategies (RPP) and in its application Islamic religious education teachers use a contextual learning model consisting of Islamic moderation discussions, Islamic moderation case studies and Islamic moderation short film screenings. This is associated with the material of Islamic religious education and ethics books which include the values of balance, justice and tolerance